2018
DOI: 10.1111/imm.12890
|View full text |Cite
|
Sign up to set email alerts
|

Acute stimulation generates Tim‐3‐expressing T helper type 1 CD4 T cells that persist in vivo and show enhanced effector function

Abstract: T-cell immunoglobulin and mucin domain 3 (Tim-3) is a surface receptor expressed by T helper type 1 (Th1) effector CD4 T cells, which are critical for defence against intracellular pathogens and have been implicated in autoimmune disease. Previous studies showed that Tim-3 expression makes Th1 cells more susceptible to apoptosis and also marks functionally impaired T cells that arise due to chronic stimulation. However, other studies suggested that Tim-3-expressing Th1 cells do not always have these properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 85 publications
(225 reference statements)
3
9
0
Order By: Relevance
“…Furthermore, the absence of Tim-3 leads to defective Akt/mTOR signaling 23 ; however, in the chronic LCMV T-cell exhaustion model, Tim-3 expression was sufficient to dampen the anti-PD-1 rescue of T-cell responses, thereby suggesting crosstalk of PD-1 and Tim-3 in exhausted T cells 23 , as discussed above. Supporting this finding is the recent report by Gorman and Colgan that acute stimulation in response to LCMV infection leads to upregulation of Tim-3 in persisting Th1-type CD4 cells, and these cells also show enhanced effector functions both in vitro and in vivo 24 .…”
Section: Tim-3 Signalingsupporting
confidence: 58%
“…Furthermore, the absence of Tim-3 leads to defective Akt/mTOR signaling 23 ; however, in the chronic LCMV T-cell exhaustion model, Tim-3 expression was sufficient to dampen the anti-PD-1 rescue of T-cell responses, thereby suggesting crosstalk of PD-1 and Tim-3 in exhausted T cells 23 , as discussed above. Supporting this finding is the recent report by Gorman and Colgan that acute stimulation in response to LCMV infection leads to upregulation of Tim-3 in persisting Th1-type CD4 cells, and these cells also show enhanced effector functions both in vitro and in vivo 24 .…”
Section: Tim-3 Signalingsupporting
confidence: 58%
“…Previous research has established inhibitory receptors to play a critical role in T cell exhaustion in chronic infections after prolonged antigen exposure (14,15,42,43). However, inhibitory receptors also have important functions and are transiently expressed during acute infections (17,24,(44)(45)(46)). Many studies have described an increased expression of inhibitory receptors on both CD8 + and CD4 + T cells during malaria infection (26,27,47,48).…”
Section: Covid-19 and Acute Malaria Infection Are Accompanied By Elevmentioning
confidence: 99%
“…Lack of FoxP3 expression after early activation in TIM-3 + cells suggested that these cells are non-suppressive and could be effector cells. Gorman and Colgan showed that, following stimulation, Th1 cells express TIM-3 and release more cytokines than TIM-3cells [17]. These proliferating TIM-3 + T cells are functionally competent and have an amplified ability to produce cytokines such as IL-2, that serves as an autocrine growth factor, that result in increased proliferation of responder T cells.…”
Section: Pd-1 Blockade Does Not Affect the Suppressive Potential Of Tmentioning
confidence: 99%